2007
DOI: 10.1080/03014460601080728
|View full text |Cite
|
Sign up to set email alerts
|

Maternal early second trimester pregnancy weight in relation to birth outcome among Bengalee Hindus of Kolkata, India

Abstract: The findings suggest a positive association between maternal early second trimester pregnancy weight and birth outcome. The present study provided an efficient cut-off point for detecting LBW. Antenatal caregivers in health institutions and community health workers in the field can use this cut-off value for screening pregnant women at early second trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…The findings complement several studies relating the effect of mother's parity on birth weight indicating that parity is the more important factor affecting birth weight and higher the parity, the more likely the lower the birth weight (Warburton and Naylor, 1971;Sanghvi and Patel, 2016). Study from other developing country indicates that birth order was one of the major factors affecting birth weight; women who were pregnant for the second and third time gave birth to neonates with higher birth weights, while women with first gravidity gave birth to neonates with lower birth weights.A possible explanation of lower birth weight among first-born infants could be a consequence of biological immaturity of the mothers as compared to later-born infants (Bisai et al, 2006). Furthermore, other variables like BL, HC, CC and MUAC indicate similar trend as observed in the BW.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The findings complement several studies relating the effect of mother's parity on birth weight indicating that parity is the more important factor affecting birth weight and higher the parity, the more likely the lower the birth weight (Warburton and Naylor, 1971;Sanghvi and Patel, 2016). Study from other developing country indicates that birth order was one of the major factors affecting birth weight; women who were pregnant for the second and third time gave birth to neonates with higher birth weights, while women with first gravidity gave birth to neonates with lower birth weights.A possible explanation of lower birth weight among first-born infants could be a consequence of biological immaturity of the mothers as compared to later-born infants (Bisai et al, 2006). Furthermore, other variables like BL, HC, CC and MUAC indicate similar trend as observed in the BW.…”
Section: Discussionsupporting
confidence: 51%
“…Older women experience an increase in the incidence of congenital abnormalities as well as maternal morbidities such as hypertension andgestational diabetes (Yogevet al, 2010;Carolan and Frankowska, 2011). However, some literature has suggested that controlling for socioeconomic status heavilyattenuates or eliminates associations of adolescence and of high parity with adverse outcomes (Sharma et al, 2008).It has been reported that primipara has higher relative risk of delivering low birth weight (LBW) babies in developing countries (Bisai et al, 2006;Lawoyin, 2007). In another study Elshibly and Schmalisch (2008) shows that primiparity is associated with an increased relative risk for LBW and that was distinctly higher when compared to the relative risk for LBW of other maternal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of thinness is frequently associated with nutri onal defi ciencies, menstrual irregularity and ea ng disorders, 43,44 and adverse reproduc ve outcomes 1,6 among adolescent girls and young women. Studies have also confi rmed that undernutri on (e.g., CED or thinness) among young women of childbearing age is a risk factor for adverse pregnancy outcomes, such as intrauterine growth-restricted or low-birth weight infants in Indian popula ons 1,45,46 . Moreover, marriage and early confi nement among adolescents are a long established custom in Indian society, with poverty and ignorance magnifying such problems 2,7,11,47 .…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of low birth weight to total births in Bam, Kerman, and Kahnuj was worse compared to other cities. From the perspective of public health, mean birth weight in a society reflects the quality of health services, prenatal care, and quality of intrauterine growth (19)(20)(21). Many maternal deaths were attributed to poorly-managed childbirth, especially in women with complicated pregnancies or childbirth.…”
Section: Discussionmentioning
confidence: 99%